Fios e fibras: vivendo a privatização da empresa de Telecomunicações do Rio de Janeiro - Iachan, Ana Christina Saraiva (2006)
This dissertation analyzer a recent event in the history od Brazil, the privatization process os the TELEBRÁS system, bringing to the forefront the memories of some of its actors, the telephone companies’ employees. This work specifically privileges the case of one company, wich was privatized in July of 1998 – Telecomunicações do Rio de Janeiro S.A. (TELERJ). The telecommunication sector is extremely relevant to understand economic and social development in the contemporary era and this thesis traces the history of TELERJ through many moments: its formation, in 1923, as a private enterprise founded by foreign capital, its transformation into a state owned company until its privatization. The (de)construction process if the state owned company model, beginning with the process of preparing to sell until the rupture of the telecommunication monopoly in 1995, is examined in a more elaborate way. To analyze the changes that followed the privatization process and its consequences for the employees, this research studies the process of social rights conquest related to work in the context of the employment society, as defined by Robert Castel (1998) and the flexibility demands as seen by Sennet (1999).